Analisis Penggunaan Penerbitan Elektronik dan Grafis pada Aplikasi E-book Wattpad - Amirah Sabrina Amirah; Rohmaniah (Perpustakaan Universitas Riau, 2024)
This research aims to investigate the use of electronic publishing and graphics in the Wattpad e-book application. Through descriptive research, namely to obtain information and describe what is currently happening using a qualitative approach, data is collected through content analysis of related documents. The research results show that electronic publishing has expanded traditional boundaries regarding publishing and provided new opportunities for authors and publishers and that readers can easily store and read book collections on their devices without the need to carry heavy physical books. The implication of this research is that the use of electronic publishing has increased due to advances in computer technology and the potential unique features it offers. Meanwhile, the development of the electronic market is driven by advances in information technology, ease of access and security of online transactions. This development has brought benefits to consumers and businesses.